Acetylation Modification Improves Immunoregulatory Effect of Polysaccharide from Seeds of Plantago asiatica L. - Le-Ming Jiang; Shao-Ping Nie; Dan-Fei Huang; Zhi-Hong Fu; Ming-Yong Xie (Journal of Chemistry)
The current study was conducted to investigate effects of acetylated Plantago asiatica L. polysaccharides (Ac-PLCPs) on their immunoregulatory activities in bone-marrow-derived dendritic cells (DCs) model. Influences of natural Plantago asiatica L. crude polysaccharide (PLCP) and Ac-PLCPs on inducing phenotypic and functional maturation on DCs were determined. The results showed that Ac-PLCPs with degree of substitution (DS) from 0.06 to 0.1 could not only stimulate the expression of surface molecules major histocompatibility complex class II (MHC II), cluster of differentiation 86 (CD86), and CD80 on DCs (P<0.01) but also increase the secretion of cytokine IL-12p70 (P<0.01). The endocytosis activity of DCs was attenuated by Ac-PLCPs treatment (P<0.01), while the mRNA expressions of chemokine receptors CCR7 and CXCR4 in DCs were significantly increased (P<0.01). Besides, DCs treated with the Ac-PLCPs showed extremely strong T cell proliferation stimulating activity (P<0.01). These data showed that Ac-PLCPs had higher maturation-stimulating activity on DCs than PLCP, which indicated that acetylation modification improved the immunoregulatory effect of PLCP.